Penerapan Material Bekas Pada Mebel Anak Usia Dini di Surabaya - Tio Sandra Gunawan (Intra, 2017)
Children are a valuable asset in family and nation. The golden days of childhood development are very important that only occurring once and should not be wasted. One solution is through PAUD (early childhood education) the curriculum is good and also has adequate facilities for both interior elements and supporting elements of furniture. Furniture used for children can not be arbitrary, and all aspects of production need to be considered such as color, ergonomics, and others. Especially material, material will affects the comfort and safety of children. This research will discussing about the application of used materials on PAUD furniture that can be useful for children with affordable budget but still safe, comfortable, and has aesthetic value. This research begins with the collection of data by interview, observation, analysis, and its application through the manufacture of furniture 1: 1. The result of this research is furniture from used materials which is suitable for early childhood and can help teaching and learning process in PAUD. The furniture includes 1 set containing 3 product that is educative tile board, shoe rack, and hand wash